Буренка и компания: [стихи] / [художники Александр Алир [и др.] - Алир Александр (Для самых маленьких, 2016)
Экземпляры: ф.6 (20170921) / Инвентарный номер: 54198 / Цена: 41.00 / Авт.знак: Б 91 / ГРНТИ: 17.82.93 / ББК: 84 (2Рос=Рус)-5